Excavation of a Roman settlement in the north-western hinterland of Aquincum (Óbuda, Hungary) at Pilisszentiván - Simon, Bence; Joháczi, Szilvia; Müller, Ákos; Rupnik, László (Dissertationes Archaeologicae, 2024)
As part of a new research project and a local history research project, a team of the Institute of Archaeological Sciences of the Eötvös Loránd University and the Archeovertex Ltd. excavated a Roman rural settlement in the territory of Pilisszentiván. The settlement is located in the northwestern hinterland of the Roman town of Aquincum (today: Óbuda, Hungary) in a scarcely investigated area. We documented the previously uncovered but unpublished remains of three buildings and made new observations on the chronology and function of the excavated settlement part.